Membentuk Generasi Pelayan: Meningkatkan Aktivitas Remaja Katolik Melalui Pelatihan Liturgi di Stasi Hati Kudus Yesus Margomulyo - Vinsensius Septa Wardana; Teresia Noiman Derung (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Catholic youth are the important future of the church. Teenagers also have a role in continuing the goals and ideals of the nation and state in the future. This research aims to increase the participation of Catholic teenagers in liturgical services at the Sacred Heart of Jesus Margomulyo Station through a structured training program. The methods used include observation and practical training regarding liturgical tools, lectors and acolyte duties. This training runs from January to June 2024 and involves Catholic teenagers in order to improve their understanding and skills in the liturgy. The research results showed an increase in understanding, self-confidence, and involvement of teenagers in church activities. This training not only strengthens their faith but also encourages a generation of Catholic teenagers to be more active in the church community. It is hoped that this program can become a model for other churches to increase youth involvement in liturgical activities.